REGULATING THE PRIVATE SECURITY IN THE NATIONAL STATES (Annual of the Faculty of Philosophy in Skopje, 2014)
This paper counterpoises a critical review of the need for regulation of the private security in the national states. The starting premise is that this sector has to be appropriately regulated with adequate laws, which usually designate the standards that need to be achieved in the engagement. In other words, the concept for the regulation should unite the different segments of the private security policies and represents the institutional expedient through which the goals can be achieved. In that notion, the regulation creates a mechanism through which the undertaken activities are realized, that would basically also mean legitimacy’ in the working process, as a central element around which the private security' policy is spinning.
Keywords: PRIVATE SECURITY; PRIVATE SECURITY SECTOR; REGULATION; ADJUSTMENT; SYNCHRONISATION